PRINCIPLES OF CALCULATION IN FARM BUSINESS ANALYSIS: FINANCIAL AND ECONOMIC PERSPECTIVES - Agus Supriono; Rizky Yanuarti; Rena Yunita Rahman; Julian Adam Ridjal; Ratih Apri Utami; Intan Kartika Setyawati (Undana Press, 2026)
Farm business analysis is an analytical approach used to examine the extent to which returns from a farming enterprise can be obtained from the costs sacrificed in the relevant farm business. There are two types of farm business analysis, namely: (a) financial analysis or private analysis and (b) economic analysis. In both financial and economic farm business analysis, the calculation does not only include actual costs or explicit costs, but also notional costs or implicit costs. In financial analysis, the estimated values of costs and revenues are based on the prevailing local real prices. In economic analysis, however, the estimated values of costs and revenues are based on shadow prices. Shadow prices are prices that would prevail in a perfectly competitive market. In this regard, it is important to study comprehensively the principles of calculation used to estimate costs and revenues in farm business analysis, both from financial and economic perspectives. This scientific article aims to provide a comprehensive explanation of these calculation principles.